Effects of partner support on life satisfaction cisgender and transgender adolescents. (20th October 2021) - Ciria-Barreiro, E; Moreno-Maldonado, C; Rivera, F; Moreno, C
Abstract: Background: Among gender minority youth the effect of family, school, peer, and community support are positively associated with emotional well-being, feelings of safety, or improved mental health. However, most research addressing the partner's role in gender minority adolescents have focused on risk behaviors (STI/HIV infection, unplanned pregnancy...) or intimate-partner violence. Because research has seldomly adopted a positive approach, little is known about the effect of partner support on transgender youth health? Methods: The sample consisted of 170 transgender and 535 cisgender adolescents (selected through a matching process) 15 to 18 years-old who participated in the 2018 HBSC survey in Spain. Emotional Support was measured using the Network of Relationships Inventory (NRI) and Life-Satisfaction with Cantril Ladder. Means comparisons, hierarchical multiple linear regression and interaction tests were performed to contrast differences between the two groups, and to check the possible buffer effect of gender identity on the relationship between partner support and life satisfaction. Results: Transgender adolescents scored lower in life satisfaction than cisgender peers. No differences were found between groups in the perception of emotional support, however emotional support was positively related to life satisfaction. Lastly, the relationship between partner support and life satisfaction was not moderated by gender identity. Conclusions: This research showed that cisgender and transgender adolescents do not have differences in partner support, and highlights the overall positive benefit of partner support for health. Using a positive approach to better understand the impact of romantic relationships during adolescence will contribute to build strong network of assets for gender minority youths' positive development. Key messages: Researching the development of trans adolescents requires the use of approaches that do not pathologize their realities. Individual and contextual assets should be considered to promote empowerment and well-being.